Comprehensive Seismicity, Seismic Sources and Seismic Hazard Assessment of Assam, North East India. Issue 2 (1st February 2020) - Bahuguna, Ashish; Sil, Arjun
ABSTRACT: In this study, an effort has been made to perform seismic hazard analysis (SHA) for the state of Assam, considering earthquake catalog collected since 1761–2015 using PSHA and DSHA methods at bed rock level. Earthquake catalog declustered and seismicity parameters (a & b) of faults estimated. The SHA performed using newly proposed modified attenuation relation and compared. Results are presented in the form of seismic hazard curve and peak ground acceleration (PGA) for each 33 district headquarters. The PGA at the bed rock level with 2%, 5%, and 10% probability of exceedance in 50 years and 100 years estimated.